1975
DOI: 10.1210/jcem-41-6-1130
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anticonvulsant Therapy on Serum Levels of 25-Hydroxy-Vitamin D, Calcium, and Parathyroid Hormone

Abstract: In 20 female patients treated for 2 to 37 years (mean :12) with anticonvulsant drugs, low serum levels of 25-hydroxy-vitamin D (25-OH-D; 6.4 +/- 3.2 ng/ml M +/- SD), relative hypocalcemia (9.2 +/- 0.4 mg/100 ml) and high levels of parathyroid hormone (PTH 277 +/- 165 pg/ml) were found compared to an age-matched control group (respectively 8.6 +/- 3.2 ng/ml, 9.6 +/- 0.3 mg/100 ml and 183 +/- 95 pg/ml) living in the same psychiatric clinic. A significant negative correlation was found between total duration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(45 citation statements)
references
References 17 publications
2
42
1
Order By: Relevance
“…These decreased concentrations have been thought to be secondary to increased hepatic degradation of the 25-hydroxy metabolite to more polar by-products with resultant increased biliary excretion of the vitamin (8)(9)(10). However, using a recycling in vitro hepatic perfusion system, we have shown that phenobarbital treatment of rats for 5 (24). These results are similar to our values of 19.5 and 20.5 nM/g liver per min in phenobarbital-treated and control rachitic perfused livers, where only a loading dose was administered.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These decreased concentrations have been thought to be secondary to increased hepatic degradation of the 25-hydroxy metabolite to more polar by-products with resultant increased biliary excretion of the vitamin (8)(9)(10). However, using a recycling in vitro hepatic perfusion system, we have shown that phenobarbital treatment of rats for 5 (24). These results are similar to our values of 19.5 and 20.5 nM/g liver per min in phenobarbital-treated and control rachitic perfused livers, where only a loading dose was administered.…”
Section: Discussionmentioning
confidence: 88%
“…The hypocalcemia, elevated levels of circulating immunoreactive parathyroid hormone, and increased amounts ofunmineralized bone or osteoid attending anticonvulsant therapy (1)(2)(3)(4)(5)(6)(7) have been attributed to derangements in vitamin D metabolism resulting in decreased serum concentrations of 25-hydroxyvitamin D3 (2-4). These decreased concentrations have been thought to be secondary to increased hepatic degradation of the 25-hydroxy metabolite to more polar by-products with resultant increased biliary excretion of the vitamin (8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs such as CBZ, PB, PRM and DPH are known to induce hepatic mixed function oxidase activity throughout the microsomal enzymes (P450) in the liver. They are thought to affect bone and mineral metabolism indirectly by increasing the metabolism of vitamin D, thereby causing vitamin D insufficiency or deficiency 2,3,6,10 . The other mechanism of the AEDs involves a direct action on bone cells, increasing bone resorption and formation.…”
Section: Palavras-chave: Drogas Antiepiléticas Indutoras Hepáticas 2mentioning
confidence: 99%
“…The most common laboratory abnormalities described in relation to AED are hypocalcaemia, hypophosphatemia, elevated levels of alkaline phosphatase (AP), reduced levels of 25-hydroxy vitamin D (25OHD) and increased serum parathyroid hormone (PTH) 3,4,10 . The chronic use of AED is a well-known cause of secondary osteoporosis 14,15 .…”
Section: Palavras-chave: Drogas Antiepiléticas Indutoras Hepáticas 2mentioning
confidence: 99%